Konsep Pembelajaran Berdiferensiasi di Sekolah Dasar: Sebuah Tinjauan Literatur Sistematis - Utari, Unga; Unga Utami (STKIP Andi Matappa Pangkep, 2024)
One of the efforts to improve the quality of learning is through practices that prioritize student-centered learning. Student-centered learning practices can be designed through the concept of differentiated instruction. However, the lack of teacher involvement in gathering data on students' learning needs and interests has resulted in learning processes that tend not to accommodate the diverse needs of students. This study aims to analyze and describe the implementation of differentiated instruction carried out in primary schools. The review process includes the collection and analysis of literature related to the application of differentiated instruction, focusing on aspects of students' learning readiness, interests, and learning profiles. The findings indicate that differentiated instruction can enhance learning effectiveness by providing more personalized and meaningful learning experiences for students. This article is expected to offer new insights and practical recommendations for teachers, schools, and policymakers in implementing differentiated instruction in primary schools.